Adipokines and their role in acute pancreatitis: Adipokines in acute pancreatitis - Rafaqat, Saira; Radoman Vujacic, Irena; Patoulias, Dimitrios; Khurshid, Huma; Klisic, Aleksandra (Journal of Medical Biochemistry, 2024)
Acute pancreatitis (AP) is characterized by an inflammatory response that leads to edema and haemorrhaging of pancreatic tissue. In severe cases, it can even result in the necrosis of pancreatic tissue following activation within the pancreas. Adipokines are biologically active molecules released by adipose tissue that have a wide-ranging impact on health and disease. Adipokines are cytokines produced not only in white adipose tissue but also in the fat surrounding the pancreas, and they play a role in the body's inflammatory response. The presence of increased adipose tissue, often associated with obesity, has been linked to a heightened systemic inflammatory response in cases of AP. According to the literature, there are many adipokines. This article summarizes the role of adipokines in AP.  Adipokines could be the promising biomarkers for both diagnostic and new therapeutic treatment strategies in AP. However, a deeper knowledge of signaling pathways of adipokines and its potential therapeutic role in AP is necessary.